2002
DOI: 10.1159/000048991
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pulmonary Arterial Smooth Muscle Structure and Reactivity during Adaptation to Extrauterine Life

Abstract: Peripheral pulmonary arteries remodel immediately after birth as pulmonary vascular resistance falls. We hypothesised that there is a link between the response to agonist stimulation and wall structure in early postnatal life. Arteries from fetal, newborn and 14-day-old piglets were mounted on a perfusion myograph. Lumen diameter and smooth muscle cell nuclear positions were recorded after sequential addition of KCl, U46619 and bradykinin. Subsequently, vessels were studied by confocal and transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Thick-walled fetal arteries remodel to thin-walled structures within days of birth (2). Using perfusion myography in conjunction with confocal microscopy we found that postnatal elongation of SMC within resistance arteries was associated with a decrease in the speed and extent of vessel constriction in response to agonist stimulation (3).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Thick-walled fetal arteries remodel to thin-walled structures within days of birth (2). Using perfusion myography in conjunction with confocal microscopy we found that postnatal elongation of SMC within resistance arteries was associated with a decrease in the speed and extent of vessel constriction in response to agonist stimulation (3).…”
mentioning
confidence: 90%
“…Previous studies have shown that piglets treated in this manner develop pulmonary hypertension, evidenced by right ventricular hypertrophy and an increase in pulmonary arterial smooth muscle (6,8 Functional studies. Perfusion myograph studies were carried out as previously described (3). Briefly peripheral pulmonary arteries immediately proximal to the alveolar region (approx.…”
Section: Origin Of Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced capacity of growth of fetal and neonatal bovine pulmonary artery adventitial fibroblasts has been demonstrated (33), and more connective tissue was present in piglet pulmonary arteries at 14 d than at birth (34). Connective tissue deposition was also augmented with postnatal age in human pulmonary arteries (35).…”
Section: Nad(p)h-mediated Omentioning
confidence: 99%